2008
DOI: 10.1111/j.1747-0285.2008.00678.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Activity of Endomorphin‐2 Analogs Incorporating Piperidine‐2‐, 3‐ or 4‐Carboxylic Acids Instead of Proline in Position 2

Abstract: Novel endomorphin-2 (EM-2) analogs have been synthesized, incorporating unnatural amino acids with six-membered heterocyclic rings, such as piperidine-2-, 3- and 4-carboxylic acids (Pip, Nip and Inp, respectively) instead of Pro in position 2. [(R)-Nip(2)]EM-2 displayed an extremely high affinity for the mu-opioid receptor with IC(50) = 0.04 +/- 0.01 nM in comparison with IC(50) = 0.69 +/- 0.03 nM for EM-2. This analog was also very potent in the aequorin luminescence-based functional calcium assay and showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 13 publications
2
17
0
Order By: Relevance
“…In particular, among the recently examined EM-2 analogues containing positional isomers of the 6-membered piperidine-carboxylic acid, replacement of Pro 2 with the chiral nipecotic acid ( viz piperidine-3-carboxylic acid) led, in accordance with the results concerning other related cyclic β-residues,14,15 to a highly active analogue 20. On the contrary, Pro 2 replacement with the achiral piperidine-4-carboxylic acid ( viz isonipecotic acid) resulted, as in the case of the here reported analogue 5 , to a practically inactive ligand 20. It can be argued that the high conformational restriction and the reduced flexibility of the 4-membered achiral 3Aze are detrimental features which prevail over the advantages which, in larger cyclic systems, derive from the presence of a β-positioned carboxylic group.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…In particular, among the recently examined EM-2 analogues containing positional isomers of the 6-membered piperidine-carboxylic acid, replacement of Pro 2 with the chiral nipecotic acid ( viz piperidine-3-carboxylic acid) led, in accordance with the results concerning other related cyclic β-residues,14,15 to a highly active analogue 20. On the contrary, Pro 2 replacement with the achiral piperidine-4-carboxylic acid ( viz isonipecotic acid) resulted, as in the case of the here reported analogue 5 , to a practically inactive ligand 20. It can be argued that the high conformational restriction and the reduced flexibility of the 4-membered achiral 3Aze are detrimental features which prevail over the advantages which, in larger cyclic systems, derive from the presence of a β-positioned carboxylic group.…”
supporting
confidence: 78%
“…Several chemical modifications performed on EMs have been described previously and many of them were focused on the Pro at position 2 12–20. The presence of Pro, the sole proteinogenic amino acid possessing a cyclic structure and a secondary amino group, represents a crucial factor in determining the structural and conformational properties of proteins and peptides.…”
mentioning
confidence: 99%
“…An earlier study showed that replacement of Tyr 1 by Dmt resulted in marked increases in receptor-binding affinity and bioactivity in numerous opioid peptide agonists and antagonists (4). Replacement of Pro 2 by alicyclic β-amino acids, pseudoprolines or piperidine-2-, -3-and -4-carboxylic acids resulted in increased affinity for the MOR and enhanced proteolytic stability (7,14,16,35). The insertion of pFPhe in place of the Phe 4 in enkephalin or endomorphins resulted in increased potency in functional assays (22,38).…”
Section: Discussionmentioning
confidence: 99%
“…5), which could serve as a-, b-, and g-amino acids, in position 2, respectively. 40 Configuration of the chiral acids, Pip and Nip, was chosen to be S and R to mimic the spatial arrangement of L-Pro present in EMs (18-20, (Table II), showed similar enhancement of metabolic stability and similar analgesic properties, which were much stronger and longer lasting than those of parent peptide EM-2.…”
Section: A Pro: a Spacer Or An Unusual Visa For Mor Selectivitymentioning
confidence: 99%